2018
DOI: 10.1097/md.0000000000009821
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for management of lower urinary tract symptoms in Parkinson's disease

Abstract: Background:Acupuncture is claimed to improve the lower urinary tract symptoms (LUTS). Currently, no systematic reviews are performed for acupuncture on LUTS in patients with Parkinson's diseases (PD). This review aims to evaluate the current evidence on the efficacy of acupuncture for the management of LUTS in PD.Methods and analyses:Eleven databases will be searched from their inception. These include PubMed, AMED, EMBASE, the Cochrane Library, 6 Korean medical databases, and 1 Chinese medical database. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Although local anesthetics, non-steroidal anti-inflammatory drugs (NSAIDs), and opioids are the common analgesics being used during ESWL in daily practice (14), no consensus has been reached on the optimal analgesic regimen. Acupuncture has long been used as a mode of analgesia (15) that improves lower urinary tract symptoms (16,17) through inducing ureteral smooth muscle relaxation (18), thereby achieving renal colic pain relief (19). Previous findings have shown that the use of acupuncture during ESWL could reduce analgesic requirement, alleviate anxiety (20)(21)(22), and improve the success rate of the procedure (23).…”
Section: Introductionmentioning
confidence: 99%
“…Although local anesthetics, non-steroidal anti-inflammatory drugs (NSAIDs), and opioids are the common analgesics being used during ESWL in daily practice (14), no consensus has been reached on the optimal analgesic regimen. Acupuncture has long been used as a mode of analgesia (15) that improves lower urinary tract symptoms (16,17) through inducing ureteral smooth muscle relaxation (18), thereby achieving renal colic pain relief (19). Previous findings have shown that the use of acupuncture during ESWL could reduce analgesic requirement, alleviate anxiety (20)(21)(22), and improve the success rate of the procedure (23).…”
Section: Introductionmentioning
confidence: 99%
“…According to a report by the World Health Organization (WHO), published in 2003, among the affections of the urinary system that have proven efficacy of acupuncture, one can mention the retention and urinary incontinence (31) . It appears that investigations involving the effect of systemic acupuncture in LUTS control have had greater investments, when compared to auriculotherapy (32)(33)(34) . On the other hand, auriculotherapy is considered to be a simpler and less costly method to be implemented in clinical practice (22) , a fact that has raised new investigations regarding the effectiveness of this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In another prospective randomized study, researchers found that the gait of PD patients improved significantly after 3 weeks of EA treatment (Lei et al, 2016). Rather clinical reports have found that acupuncture can improve complications caused by PD, such as lower urinary tract symptoms (Kim et al, 2018), fatigue (Corbin et al, 2016; Kong et al, 2018), rigidity and balance (Toosizadeh et al, 2015), swallowing reflex latency (Fukuda et al, 2016), sleep disorders (Landgren et al, 2011), and so on.…”
Section: Parkinson’s Diseasementioning
confidence: 99%